2014
DOI: 10.7196/samj.7299
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B and HIV co-infection in pregnant women: Indication for routine antenatal hepatitis B virus screening in a high HIV prevalence setting

Abstract: Background. Sub-Saharan Africa is endemic for hepatitis B virus (HBV) and human immunodeficiency virus (HIV) infections. HBV/HIV co-infection in women of reproductive age is of clinical and public health importance because these women constitute a significant reservoir for horizontal and perinatal HBV transmission. Childhood HBV vaccination from 6 weeks of age protects most children against chronic HBV infection. However, infants born to HBV/HIV co-infected women are more likely to be infected perinatally, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 15 publications
4
24
4
1
Order By: Relevance
“…Furthermore, the prevalence of HBV/HIV co-infection among pregnant women found in our study was higher than the previous reports in Nigeria (0.24%), Ethiopia (0.6%) and Cameroon (1.5%) [24, 33, 34]. However, the prevalence of HBsAg in the current study was lower than that reported from a recent study among pregnant women in South Africa (3.1%) [35]. The observed low HBV/HIV co-infection rates in settings of high HBV endemicity could be explained by the fact that the main routes of transmission of HBV in Sub-Saharan Africa could be vertical and likely occurs in early childhood.…”
Section: Discussioncontrasting
confidence: 89%
“…Furthermore, the prevalence of HBV/HIV co-infection among pregnant women found in our study was higher than the previous reports in Nigeria (0.24%), Ethiopia (0.6%) and Cameroon (1.5%) [24, 33, 34]. However, the prevalence of HBsAg in the current study was lower than that reported from a recent study among pregnant women in South Africa (3.1%) [35]. The observed low HBV/HIV co-infection rates in settings of high HBV endemicity could be explained by the fact that the main routes of transmission of HBV in Sub-Saharan Africa could be vertical and likely occurs in early childhood.…”
Section: Discussioncontrasting
confidence: 89%
“…It is also noteworthy, that none of the HBV infected pregnant women in our study sample had HIV co-infection. Unlike our finding, other studies within the region have reported HIV among HBV infected pregnant women (37,38). Our result might be explained by the fact that all our HIV infected women were already taking ART.…”
Section: Discussioncontrasting
confidence: 99%
“…Routine maternal screening for HBV during pregnancy would yield benefits for both mother and child, including clinical assessment and appropriate treatment for adult infection, and implementation of measures to reduce both vertical and within-household transmission [11]. Ongoing evaluation of the risks and benefits of the timing of the first HBV vaccine dose is required.…”
Section: Discussionmentioning
confidence: 99%